To solve the equation a^x - x^c = b, we first rewrite it as f(x) = a^x - x^c - b = 0. The process starts with an initial guess for x, then refines the guess using the formula: x_{n+1} = x_n - f(x_n) / f'(x_n) where f'(x) is the derivative of f(x), calculated as f'(x) = a^x * ln(a) - c * x^(c-1). By repeatedly updating x with this formula, the process gradually approaches a solution when the difference between successive values of x becomes very small. This method is particularly effective for solving equations that involve both exponential and polynomial terms.
@Misha-g3b4 ай бұрын
2.
@민우김-f4n3 ай бұрын
X=2 9^x-x^4=65 65=9^2-4^2 81-16=65 X=2
@shannonmcdonald75843 ай бұрын
2. Just by looking. But you want the other 3 I solutions don't you?